System biology approach to identify the novel biomarkers in glioblastoma multiforme tumors by using computational analysis - Alqahtani, Safar M.; Altharawi, Ali; Alabbas, Alhumaidi; Ahmad, Faisal; Ayaz, Hassan; Nawaz, Asia; Rahman, Sidra; Alossaimi, Manal A. (Frontiers in Pharmacology, 2024)
The most common primary brain tumor in adults is glioblastoma multiforme tumor (GBM), accounting for 45.2% of all cases. The characteristics of GBM, a highly aggressive brain tumor, include fast cell division and a propensity for necrosis. Regretfully, the prognosis is extremely dismal, with only 5.5% of patients surviving after diagnosis. To eradicate these kinds of complicated diseases, a great deal of focus is placed on developing more effective drugs and pinpointing precise pharmacological targets. To find appropriate biomarkers for drug discovery, this entails considering a variety of factors, including illness states, gene expression levels, and interactions between proteins. Using statistical techniques like p-values and false discovery rates, we identified differentially expressed genes (DEGs) as the first step in our research for promising biomarkers in GBM. Out of the 132 genes, 13 showed upregulation and only 29 showed unique downregulation. No statistically significant changes in the expression of the remaining genes were observed. MMP9 was shown to have the greatest degree in the hub biomarker gene identification, followed by POSTN at 11 and HES5 at 9. The significance of each hub biomarker gene identification in the initiation and advancement of glioblastoma multiforme tumor was brought to light by survival analysis. Many of these genes participate in signaling networks and function in extracellular areas, as demonstrated by enrichment analysis. We identified the transcription factors and kinases that control proteins in the protein-protein interactions (PPI) of the differentially expressed genes. Furthermore, we discovered drugs connected to every hub biomarker. It is an appealing therapeutic target for inhibiting MMP9 involved in GBM. Molecular docking investigations indicated that the chosen complexes (Carmustine, Lomustine, Marimastat and Temozolomide) had a high binding affinities. Whereas a mean RMSD value for Carmustine complex and Marimastat complex is 4.2 Å and 4.9 Å. While the Lomustine and Temozolomide complex system showed an average RMSD of 1.2 Å and 1.6 Å respectively. Additionally, high stability in RMSF analysis has been observed with no structural confirmational changes among the atomic molecules. Thus, these In silico investigations develop a new way for future experimentalists to target lethal diseases in future.